Clinical Tips and Tricks: Capnography in the Emergency Department: A primer / Conseils et astuces cliniques : la capnographie au service des urgences — notions de base - Greenbaum, Hugh (Canadian Journal of Emergency Nursing / Journal canadien des infirmières d’urgence)

(untitled) (Pappin Communications, 2025)
Capnography is an underappreciated tool in the Emergency Department. Continuous monitoring of a patient’s CO2 output provides insights into their ventilatory, perfusion, and metabolic status at the bedside. Since it is a continuous process, capnography can often warn of dangerous conditions, especially deteriorations, seconds to minutes before other modalities. This article briefly reviews the physiology behind CO2 production, how capnography monitors work, and what they tell us. Key waveforms are reviewed, with emphasis on those that may impact immediate patient care decisions. The remainder of the article briefly discusses various clinical presentations and how the associated capnography measurements, along with patient history and other diagnostic tools, can provide early notice of life-threatening conditions or deterioration.